THE IMPLEMENTATION OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL TO IMPROVE STUDENTS' CRITICAL THINKING ABILITY - Nurlaelah, Nurlaelah; admin, admin (Teaching English as a Foreign Language Overseas Journal, 2023)
The problem in this research is the low levels of students' critical thinking skills in class XII. The formulation of the problem in this study is how to apply the Problem Based Learning (PBL) learning model to improve students' critical thinking skills in English class XII UPT SMKN 4 Pangkep. This study aims to describe the Implementation of the Problem Based Learning (PBL) learning model in improving students' critical thinking skills in English class XII. The research approaches used is classroom action research (CAR), which includes the stages of planning, implementing, observing and reflecting. The subjects in this study were researchers as teachers and class XII teachers as observers at UPT SMKN 4 Pangkep, totaling 27 people. The focus of the research is the Implementation of the Problem Based Learning (PBL) learning model and students' critical thinking skills. Data collection is done through observation and documentation. The data analysis techniques used is a qualitative data analysis technique to process data about the results of observation of teacher activities and student activities during the giving of actions. The results of research on the first cycle of teacher activity and student activity are in the sufficient category. In cycle II, the Implementation of the Problem Based Learning (PBL) learning model experienced an increase, namely for teacher activities and students’ activities reaching a good category. Thus, it can be concluded that the Implementation of Problem Based Learning (PBL) can improve students' critical thinking skills.